All in a day's work: Towards improved understanding of safety leadership during regular safety‐related tasks in mining. Issue 2 (23rd October 2020) - Donovan, Sarah‐Louise; Salmon, Paul M.; Horberry, Tim; Lenné, Michael G.
Abstract: This article examines safety leadership during regular safety‐related tasks conducted across a mining work system. Applying a systems‐thinking methodology, a modified version of the critical decision method (CDM) interview technique was used to examine decision‐making and behavior in association with five safety‐related tasks executed across the work system; hazard identification, inspections, standard operating procedure development, task observation and return to work coordination activities. Data were mapped onto Rasmussen's risk management framework to explore the characteristics of safety leadership decision‐making and behavior which occurred across the work system to support successful task execution. Vertical integration was present and was associated with a core set of decision‐making elements and leadership behaviors that facilitated the communication and exchange of information within and across the work system in association with tasks executed. In addition, different profiles of decision‐making characteristics and behavioral engagement were evident at different system levels, which indicated variability in safety leadership was required to support successful task execution across the work system. Task type was found to influence safety leadership, with structured tasks demonstrating less intensive decision‐making and behavioral engagement requirements than unstructured tasks. The findings add to the knowledge base on safety leadership through improved understanding of the concept, its occurrence across tasks and work system levels, and the factors which influence it to support safe system functioning. Future research endeavors and practical implications are discussed.